Media Visual Sebagai Alat Bantu Literasi Menulis Di Era Digital - Anita Candra Dewi (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
The development of digital technology has brought significant changes to the world of education, particularly in the development of students' writing literacy. Visual media has become a tool with significant potential to support the writing learning process, especially for students at the elementary level. This study aims to examine in depth the role and effectiveness of visual media in improving writing literacy skills in the digital era through a literature review approach. Data were collected from various relevant national and international literature sources. The analysis shows that the use of visual media, such as digital images, infographics, animations, and interactive videos, can increase students' motivation, imagination, and critical thinking skills in the writing process. Furthermore, visual media helps facilitate the understanding of abstract concepts, enriches vocabulary, and encourages creative collaboration among students. This study also found that the use of visual media requires teacher support in digital literacy and appropriate lesson planning. Thus, visual media can be an innovative solution to improving the quality of students' writing literacy if effectively integrated into the curriculum and teaching strategies.